An update on the intramedullary implant in limb lengthening: A quinquennial review Part 1: The further influence of the intramedullary nail in limb lengthening. (November 2022) - Calder, Peter R; Wright, Jonathan; Goodier, W David
Abstract: The goal of limb lengthening is to restore length to bone, safely stretch soft tissues and improve quality of life with minimal complications. Traditionally this was achieved with the use of external fixators, associated with complications related to pin site tethering and infections, joint stiffness and regenerate deformity and fracture following frame removal. The duration of treatment also impacts on patient mental health and well-being. In order to reduce external fixator time, intramedullary nails have been introduced as an adjunct, either at the initial surgery or after completion of lengthening. Complications related to the external fixator still remained and innovation has led to the popularisation of the intramedullary lengthening nail. The lengthening mechanism of the nail can be divided into those with ratchet systems and those driven by motors. In the ratchet group, patients are required to manually rotate their limb, with movement at the osteotomy site, in order to create forward movement. This was often associated with pain, and in some cases led to the requirement of general anaesthesia to enable rotation and continuation of lengthening. Further issues were reported related to lengthening rate control. Once the nail had lengthened sufficiently for the osteotomy to disengage, rapid lengthening termed a 'runaway' nail could occur. The nails were limited to forward movement, and once length was gained it could not be retracted, leading to poor regenerate formation and soft tissue contractures. The introduction of the Fitbone implant utilised a transcutaneous electrical conduit, powered by a high frequency electrical signal, enabling more control over the lengthening. The Precice intramedullary lengthening system is controlled by the use of an external device with two rotating neodymium magnets, which produce rotation of a third magnet in the nail. By altering the direction of the magnet rotation, the lengthening can be controlled both forwards and backwards with sub-millimetre precision. Following initial excellent outcomes published, the use of the lengthening intramedullary nail has become accepted by many as the implant of choice in limb lengthening. The aim of this article comes in two parts. The first to highlight the latest research and clinical results in the last five years using an intramedullary implant during limb lengthening, and the second to report the outcome in extended surgical indications and further implant innovation.